EKSISTENSI SELEKTOR TERUKUR PADA FUNGSI BERNILAI HIMPUNAN DI DALAM RUANG BANACH TAK SEPARABEL - Mohamad Muslikh (Universitas Jenderal Soedirman, 2012)
In the Kuratowski-Ryll Nardzewski theorem, measurable selector of the set-valued functions exist if the value of set-valued function is a subset of a separable Banach spaces. In this article show that the set-valued function has a measurable selector in non separable Banach spaces.